Effect of medicated thread moxibustion on apoptosis of hippocampal neurons in rat models of chronic cerebral ischemic vascular dementia - Weilan, Qin; Yan, Yan; Xuemei, Liu; Wei, Shen; Xiaohan, Liu; Qingke, Ma; Ying, Wang; Xianglan, Jin (Cellular and Molecular Biology, 2018)
To investigate the effect of medicated thread moxibustion onapoptosis in hippocampal neuronsin a rat model of chronic cerebral ischemic vascular dementia. A total of 40 male Wistar rats were randomly divided into normal group and sham-operated group (7 rats each), and rat model of chronic cerebral ischemic vascular dementia (14 rats). The model group rats were treated with medicated thread moxibustion two weeks after surgery, once a day, with one day break every six days, (24 times in all)and an observation period of 4 weeks. At the end of therapy, H&E staining was used to monitor changes in the neurons in CA1 area of the rat hippocampus. Changes in related indexes such as Bax, Bc1-2 and C-fos of neuron apoptosis in hippocampus CA1 area were determined by immunohistochemistry, while protein expression was semi-quantitatively assayed using imaging analysis technique. There was significant hippocampal neuronal necrosis six weeks after model establishment, but the necrosis was milder in rats in the medicated thread moxibustion group. Bax and C-fos were positively expressed and significantly higher in the hippocampus of chronic cerebral ischemic vascular dementia rats (model group) than in the medicated thread moxibustion group after treatment (p <0.01). The expression of Bcl-2 was increased in the medicated thread group after treatment, and was higher in the model group, but comparable to that in the sham-operated group (p=0.975>0.05). Medicated thread moxibustion alleviates hippocampal neuronal necrosis, inhibits neuron apoptosis in hippocampus CA1 area, protects nerves, and maintains relative equilibrium inBax/Bcl-2 through down-regulation of C-fos and Bax and up-regulation of Bcl-2. Thus, cell apoptosis-related pathway may be one of its mechanisms of action.